Ti surface doping of LiNi0.5Mn1.5O4−δ positive electrodes for lithium ion batteries. Issue 13 (13th February 2018) - Ulu Okudur, F.; D'Haen, J.; Vranken, T.; De Sloovere, D.; Verheijen, M.; Karakulina, O. M.; Abakumov, A. M.; Hadermann, J.; Van Bael, M. K.; Hardy, A.
Abstract : LiNi0.5 Mn1.5 O4− δ surface is doped with Ti ion maintaining the spinel structure at 500 °C, higher annealing temperatures cause Ti diffusion from surface towards the core. Abstract : The particle surface of LiNi0.5 Mn1.5 O4− δ (LNMO), a Li-ion battery cathode material, has been modified by Ti cation doping through a hydrolysis–condensation reaction followed by annealing in oxygen. The effect of different annealing temperatures (500–850 °C) on the Ti distribution and electrochemical performance of the surface modified LNMO was investigated. Ti cations diffuse from the preformed amorphous 'TiO x ' layer into the LNMO surface during annealing at 500 °C. This results in a 2–4 nm thick Ti-rich spinel surface having lower Mn and Ni content compared to the core of the LNMO particles, which was observed with scanning transmission electron microscopy coupled with compositional EDX mapping. An increase in the annealing temperature promotes the formation of a Ti bulk doped LiNi(0.5− w ) Mn(1.5+ w )− t Ti t O4 phase and Ti-rich LiNi0.5 Mn1.5− y Ti y O4 segregates above 750 °C. Fourier-transform infrared spectrometry indicates increasing Ni–Mn ordering with annealing temperature, for both bare and surface modified LNMO. Ti surface modified LNMO annealed at 500 °C shows a superior cyclic stability, coulombic efficiency and rate performance compared to bare LNMO annealed at 500 °C when cycled at 3.4–4.9 V vs. Li/Li + . The improvements are probably due to suppressed Ni and Mn dissolution with Ti surface doping.